IMPLEMENTASI PEMBELAJARAN BERBASIS TEMATIK PADA PROGRAM STUDI PENDIDIKAN GURU MADRASAH IBTIDAIYAH FAKULTAS TARBIYAH UNIVERSITAS HASYIM ASY’ARI TEBUIRENG - Hosna, Rofiatul; Mahsun, Ali; Dahlan, Encep (Al Tadib : Jurnal Ilmu Pendidikan, 2016)
This study examines and answers three problems: (1) processes, (2) implementation, and (3) factors inhibiting/supporting the implementation of the thematic learning in PGMI department of the faculty of UNHASY Tebuireng. By applying qualitative descriptive method, the research team tried to explore the data to find answers to the focus lifted. Results of this research are, (1) the process of learning at PGMI Department of Tarbiyah Faculty UNHASY Tebuireng Jombang before implementation of thematicbased learning has not been determined based on the kind of skills that theme; lack of election materials research, competence standard, basic competence and indicator; undetermined sub-skills-based theme; and yet the formulation of indicators of learning outcomes, (2) implementation of the thematic-based learning in PGMI Department of Tarbiyah Faculty UNHASY Tebuireng Jombang has contained provisions kinds of subjects and types of skills that are combined; and (3) Factors supporting the implementation of the thematic-based learning in PGMI Department of Tarbiyah Faculty UNHASY Tebuireng is easily understood by students due to the learning process fun; more emphasis on talents, interests and needs of students; students have direct experience, while inhibiting factor is the mastery of the faculty in understanding the learning material thematic, meaning less master lecturers in depth elaboration on thematic learning themes that will find it difficult to associate the theme with the subject matter of each course. Keywords: Thematic Learning 1 Dosen Fakultas Tarbiyah Universitas Hasyim Asy’ari Tebuireng